2007
DOI: 10.1189/jlb.1106697
|View full text |Cite
|
Sign up to set email alerts
|

Chemokine stromal cell-derived factor-1 induction by C/EBPβ activation is associated with all-trans-retinoic acid-induced leukemic cell differentiation

Abstract: Stromal cell-derived factor-1 (SDF-1/CXCL12) is one of the essential chemokines, which mediates hematopoietic differentiations. However, the mechanism by which SDF-1 expression is regulated in granulocyte differentiation is poorly understood. Here, we suggest a novel mechanism by which all-trans-retinoic acid (ATRA) induces the expression of SDF-1 during the differentiation of promyelomonocytic leukemic U937 cells. Moreover, we also demonstrate that activation of transcription factor C/EBPbeta by ATRA regulate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 39 publications
0
14
0
Order By: Relevance
“…[35][36][37][38] Moreover, c/ EBPβ induces CXCL12 during leukemic cell differentiation. 8 The proximity between c/EBPβ and GR binding sites suggested an interaction between both factors. [39][40][41] Indeed, it has been reported that an increase in GR and c/EBP activity correlates with cell cycle arrest in confluent fibroblasts.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…[35][36][37][38] Moreover, c/ EBPβ induces CXCL12 during leukemic cell differentiation. 8 The proximity between c/EBPβ and GR binding sites suggested an interaction between both factors. [39][40][41] Indeed, it has been reported that an increase in GR and c/EBP activity correlates with cell cycle arrest in confluent fibroblasts.…”
Section: Discussionmentioning
confidence: 98%
“…CXCL12 plays pleiotropic functions in organogenesis, developmental or pathologic angiogenesis, and hematopoietic myeloid and lymphoid cell homing and differentiation. [6][7][8][9] CXCL12 presents six different isoforms (α, β, γ, δ, ɛ, and ϕ), generated by alternative splicing of a single gene. 10,11 These CXCL12 splice variants all share the same first three exons but contain different fourth exons that may have functional differences.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…pGL3B-SDF-1-luc (À1914 to +1) was described previously [17]. AP-1 luc was generously provided by J.W.…”
Section: Plasmid Constructs and Reagentsmentioning
confidence: 99%
“…pGL2B/hSHP-Luc (-2.2 kb) was kindly provided by Dr. Heung Sik Choi (Chonman National University, Korea). pCMX1/c-Jun, pcDNA3/p65, pGL3B/p21-Luc (-2300), or pcDNA3/HA/SHP was previously described, each other (Jang et al, 2001;Choi et al, 2004;Kim et al, 2007;Park et al, 2007).…”
Section: Plasmid Reagent and Antibodiesmentioning
confidence: 99%